Pengaruh Harga terhadap Minat Beli Konsumen dengan Gratis Ongkos Kirim sebagai Variabel Intervening pada Aplikasi Shopee (Studi pada Mahasiswa Fakultas Ekonomi Universitas Sulawesi Barat) - S, Purnama Sari; Radjab, Enny; Sumarsih, Sumarsih (Movere Journal, 2024)
This research aims to determine the effect of price on consumer buying interest with free shipping as an intervening variable in the Shopee application. This type of research is quantitative. The location of this research is at the economics faculty of the University of West Sulawesi. The population in this study were consumers who made purchases on the Shopee application at the Faculty of Economics, West Sulawesi University, so in determining the sample for this study the Hair formula was used. The number of respondents obtained was 60. Data analysis was carried out using the SmartPLS 3.2.9 statistical method. The results of this research show that price has a significant effect on consumer buying interest, Price has a significant effect on free shipping, Free shipping has a significant effect on consumer buying interest and Price does not have a significant effect on consumer buying interest through free shipping.